2021
DOI: 10.3390/antibiotics10050590
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Belgian and Dutch Broiler Farmers Aimed at Antimicrobial Stewardship and Disease Prevention

Abstract: A reduction in antimicrobial use (AMU) is needed to curb the increase in antimicrobial resistance in broiler production. Improvements in biosecurity can contribute to a lower incidence of disease and thereby lower the need for AMU. However, veterinary advice related to AMU reduction or biosecurity is often not complied with, and this has been linked to the attitudes of farmers. Behavior change promoted by coaching may facilitate uptake and compliance regarding veterinary advice. Thirty broiler farms in Belgium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
12
0
3
Order By: Relevance
“…Using the BioCheck.UGent tool to score and assess the biosecurity practices of 58 Irish farrow to finish pig farms, biosecurity practices accounted for 8% and 23% of piglet and finisher mortality, respectively [ 59 ]. Furthermore, when the BioCheck.UGent tool was used to score 30 Dutch and Belgian broiler farms and subsequently educate farmers on improving their biosecurity and on antimicrobial stewardship, a 6% increase in biosecurity and 7% reduction of AMU, without negative effects on production parameters, was reported [ 60 ]. On the European level, the effective implementation of different alternative measures in pig production, such as improvement of biosecurity, vaccination, improved feeding, and health care, has resulted in a significant reduction in AMU [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the BioCheck.UGent tool to score and assess the biosecurity practices of 58 Irish farrow to finish pig farms, biosecurity practices accounted for 8% and 23% of piglet and finisher mortality, respectively [ 59 ]. Furthermore, when the BioCheck.UGent tool was used to score 30 Dutch and Belgian broiler farms and subsequently educate farmers on improving their biosecurity and on antimicrobial stewardship, a 6% increase in biosecurity and 7% reduction of AMU, without negative effects on production parameters, was reported [ 60 ]. On the European level, the effective implementation of different alternative measures in pig production, such as improvement of biosecurity, vaccination, improved feeding, and health care, has resulted in a significant reduction in AMU [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…У наукових публікаціях є повідомлення про інфікування птиці через контаміновані мікроорганізмами корми і воду. Останні наукові дослідження підтверджують, що контамінована вода є важливим фактором ризику для здоров'я птиці (Caekebeke et al, 2021). Застосування екологічно-безпечних методів знезараження питної води є важливою умовою забезпечення епізоотичного благополуччя в умовах птахогосподарств.…”
Section: результати та їх обговоренняunclassified
“…However, they may also reflect variations in the attitude towards ABU of farmers and veterinarians, which are not necessarily linked to the true animal health situation. Several studies have shown that there is a link between the attitude towards antibiotics and antibiotic use [ 22 , 46 , 47 ].…”
Section: Quantitative Insights In Antimicrobial Use In Pigs In Europementioning
confidence: 99%